2020
DOI: 10.1136/vetreco-2019-000339
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between expression pattern of vitamin D receptor, 1 alpha‐hydroxylase enzyme, and chemokine RANTES genes and selected serum parameters during transition period in Holstein dairy cows

Abstract: ObjectivesThe objective of the present study was to evaluate the pattern of genetic expression of vitamin D receptor (VDR), 1 alpha-hydroxylase (1α-OHase) enzyme and chemokine regulated on activation normal T-cell expressed and secreted (RANTES) in peripheral blood of Holstein dairy cows during transition period.MethodsBlood samples were collected from 16 Holstein dairy cows at 3 weeks prior expected date of delivery (EDD), at the day of parturition, and 3 weeks post-partum for assessment of expression profile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
(64 reference statements)
0
3
0
1
Order By: Relevance
“…Additionally, in contrast to cows with sub-clinical endometritis, the gene expression profiles of C3 , CXCL8 , LTF , TLR2 , and TRAPPC13 were temporally changed in healthy cows’ circulating WBC during the postpartum period [ 57 ]. CCL5 gene expression did not significantly alter between the three different time periods during the transition phase [ 18 ]. In goats, the LTF gene for mastitis resistance was discovered to have an up-regulated expression profile in Damascus goats [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, in contrast to cows with sub-clinical endometritis, the gene expression profiles of C3 , CXCL8 , LTF , TLR2 , and TRAPPC13 were temporally changed in healthy cows’ circulating WBC during the postpartum period [ 57 ]. CCL5 gene expression did not significantly alter between the three different time periods during the transition phase [ 18 ]. In goats, the LTF gene for mastitis resistance was discovered to have an up-regulated expression profile in Damascus goats [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was previously believed that problems with general health at this time had a secondary impact on immunological response. However, when new cellular and molecular immunological pathways emerged, these issues and how they affected the immune system started to assume a more definite molecular reality [ 18 ]. Innate immunity supports host genetic resistance primarily, providing defense against pathogens without vaccination or exposure to illnesses [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Роль кальция и фосфора, а также витамина D в организме молочных коров хорошо изучена и достаточно полно освещена в отечественной и зарубежной как зоотехнической, так и ветеринарной литературе [3,5,16]. Снижение уровня кальция в крови приводит к нарушению многих функций органов и систем организма крупного рогатого скота [21,22,25,27,28,30,32,34,35].…”
Section: Latin Clinical Terms In Veterinaryunclassified
“…Xiao et al, (1998) found that in cows, E2 secretion is highest at estrus thus; the greatest expression of VEGF mRNA expression at estrus may be stimulated by E2 Saed et al, (2020). elicited that prior to parturition by 3 weeks the expression level of RANTES gene increased while at time of parturition the expression of the gene was down regulated Porwal et al, (2021).…”
mentioning
confidence: 98%